Perencanaan Pengelolaan Sumberdaya Lahan yang Terkena Dampak Penggunaan Lahan untuk Penembangan Kapur - Oteng Haridjaja; Wiwik Dwi Haryanti; Rina Oktaviani (Institut Pertanian Bogor, 2011)
The need of cement industry mine material to support the requirements on agricultural land resource as livelihood is two different interest that have a potential to emerge conflict of interest on nature resource utilization. Knowing the nature and human resource potentials as well as determining the direction of utilization planning strategy for sustainable land management. Research was carried out from November 2008 - April 2009. This is a descriptive qualitative study to describe the field condition. For determining sustainable land utilizationand management priority was used AHP by pair elements comparison method. General condition explained that land utilization for ecologically agriculture commodities is on appropriate land: un-suitability (NS), marginally suitability (S-3t, and S-3gt) for seasonal plants, as well as un-suitability (NS), marginally suitability (S-3te), and moderatly suitability (S-2te) for annual plants. The agricultural, industrial, and husbandry commodities that have proper economic potential is cassava, long bean, cucumber, mangoes, wood (albasia), tapioca industry, and goats husbandry. Main job as farmers is 85 %, 83°/o don't have an own land so they need an agricultural land. It is very important for their who have livelihood as a paisant, 72°/o moreover for theirs who were in a productive age. Result of AHPto determine the direction of land utilization and management pre, post, and non mining land showed that the stakeholders group who have important role on all land condition is the corporate. Priority ecology aspect on pre and post mining, socially aspect is on non-mining land utilization and management, the main choice for non-mining land utilization and management is food plants. Although value priority of bio-fuel plantation is higher than value priority of food plants, but food plants have more useful in social and economic. Priority pre-mining land utilization and management is food plants, and post-mining is land management based on sustainable environment.